DETERMINING THE DEMAND FOR MSME CREDIT THROUGH MACROPRUDENTIAL INCENTIVE POLICIES AS AN ECONOMIC RECOVERY EFFORT - Famela Galuh Dewi Agustiya; Fitri Juniwati Ayuningtyas (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
A bank is a financial institution that plays an important role in maintaining economic stability, supporting economic growth and facilitating financial activities. One of the efforts made by the banking sector is to channel credit to Micro, Small and Medium Enterprises (MSMEs) so that they can develop. This study aims to see how the influence of Non Performing Loan (NPL), Lending Interest Rate, Inflation and Macroprudential Incentive Policy on MSME credit demand in Indonesia. The research period is from 2018 to 2022. This research was conducted using secondary data obtained from the Central Bureau of Statistics, Bank Indonesia and the Financial Services Authority. The data analysis technique used is multiple linear regression. The results of this study indicate that the Non Performing Loan (NPL) variable has no significant effect on MSME loan demand in Indonesia, while the loan interest rate variable has a negative and significant effect on MSME loan demand in Indonesia and the inflation variable and macroprudential incentive policies have a significant effect on MSME loan demand in Indonesia. The conclusion is that the existence of Macroprudential Incentive Policy can increase the demand for MSME loans in Indonesia, this can have an impact on national economic growth.